Rice Production, Consumption and Economic Development in Nigeria - Otto, Godly (Annals of Spiru Haret University. Economic Series, 2021)
In recent times, rice production has become a topical issue in national discourse in Nigeria. Rice is a major staple food in all the regions of Nigeria. Over the years, Nigeria has imported rice from different countries to supplement local production, thereby putting pressure on the Nigeria foreign exchange. Since 2018, the Central Bank of Nigeria made policies aimed at curtailing the importation of some agricultural products including rice, by ordering the closure of land borders till further notice. The aim of the policy was to restrict the dumping of products such as rice into the country, which could generate an unfair competition with local rice producers. It is against this backdrop that this work investigated the effect of rice production and consumption on economic development in Nigeria, from 1986 to 2018. The data were sourced from the Central Bank of Nigeria Statistical Bulletin. To establish the empirical nexus between rice production, consumption and economic development in Nigeria, the work used the following econometrics tools of data analysis OLS, Unit root test, Johansen Cointegration and Vector Error Correction Model (VECM). The findings of the study prove that there is a significant relationship between rice production, consumption and economic development in Nigeria. In addition, the OLS result established that the relationship between rice import and the gross domestic product in Nigeria is statistically significant. The unit root test results justifies that all the model variables were non-stable at levels but gained stationarity after first difference. The Johansen Cointegration test empirically established that there is a long run convergence between the variables in the model, while the VECM result attested that the model variables are jointly instrumental in eliciting long-run equilibrium. From the foregoing, government is encouraged to support the mechanization and modernisation of rice production in Nigeria, including the introduction of modern equipment, pesticides and improved seedlings needed by rice farmers to increase rice production. This may be achieved through the provision of cheap credits to rice farmers.